Plastrum Testudinis Extracts Promote NSC Differentiation into Dopaminergic Neuron by Regulating the Interaction of TET1 and FoxA2. (20th April 2020) - Zhong, Jun; Ye, Sen; Zhou, Xiaoli; Huang, Jiapei; Li, Xican; Zhang, Saixia; Zhou, Jianhong; Chen, Dongfeng; Li, Caixia
Abstract : In recent years, stem cells have gained much attention for the treatment of neurodegenerative diseases. However, inducing neural stem cell directionally differentiation is a difficult problem in the treatment of Parkinson's disease (PD) by stem cell therapy. Plastrum Testudinis (PT) can enhance the number of TH-positive neurons in the PD rat brain substantia nigra, but the underlying mechanism has not been clarified. Here, we aimed at further investigating the mechanism by which PT can promote NSC differentiation into dopaminergic neurons. A rat model of PD was used for detecting the effect of PT on the rat brain substantia nigra in vivo. The results showed the expressions of tyrosine hydroxylase (TH) and TET1 enzyme were increased after treatment with PT. Consequently, Plastrum Testudinis extracts (PTEs) were used for inducing NSC differentiation into dopaminergic neurons ex vivo. During differentiation of NSCs induced by PTE, TH expression was increased, with a concomitant increase in both TET1 and FoxA2. Next, we performed coimmunoprecipitation analysis to examine the interaction between TET1 protein and FoxA2 protein. Our results show that PTE can increase the binding rate of TET1 and FoxA2. Thus, our findings show that PTE can increase the efficiency of NSCs to directionally differentiate into dopaminergic neurons and provide experimental evidence for PT in the treatment of Parkinson's disease.